(untitled) (Journal of Economic Research & Business Administration, 2015)
In the given article it is considered a step-by-step mechanism of human capital management. The concept of ‘capital’ is defined; the differences between physical and human capitals are disclosed. Here it is represented the algorithm of human capital development and the system of human capital and society development, approving, that human capital belongs to the social and economic category. It is especially underlined the significance of human capital management that favours to increase effectiveness of its usage that, hence, increases competitiveness of national economy of the RK and ensures stable development of the nation.